Makna dalam Acara Ritual Adat Galih Tulang sebagai Bentuk Implementasi Hukum Lokal di Sumba Barat Daya (International Forum of Researchers and Lecturers, 2024)
The law of engagement is a concept that has existed since ancient times. In the past, engagements often relied on customary law and social norms applicable in a particular society. However, with the increasing development of society and trade, there is a need to have more formal legal rules to regulate agreements and agreements. The term